THE EVOLUTION OF GROUNDWATER IN THE TYRRELL CATCHMENT, SOUTH-CENTRAL MURRAY BASIN, VICTORIA, AUSTRALIA - Petrides B.; Cartwright I.; Weaver T.R. (My University, 2006)
The Tyrell catchment lies on the western margin of the Riverine Province in the south-central Murray Basin, one of Australia’s most important groundwater resources. Groundwater from the shallow, unconfined Pliocene Sands aquifer and the underlying Renmark Group aquifer is saline (total dissolved solids up to 150,000 mg/L) and is Na-Cl-Mg type. There is no systematic change in salinity along hydraulic gradients implying that the aquifers are hydraulically connected and mixing during vertical flow is important. Stable isotopes (18O+2H) and Cl/Br ratios indicate that groundwater is entirely of meteoric origin and salts in this system have largely been derived by evapotranspiration of rainfall with only minor halite dissolution, rock weathering (mainly feldspar dissolution), and ion exchange between Na and Mg on clays. Similarity in chemistry of all groundwater in the catchment implies relative consistency in processes over time, independent of any climatic variation. Groundwater in both the Pliocene Sands and Renmark Group aquifers yield ages of up to 25 ka. The Tyrrell Catchment is arid to semi-arid and has low topography. This has resulted in relatively low recharge rates and hydraulic gradients that have resulted in long groundwater residence times.
Keywords: SALINITY; TYRRELL CATCHMENT; MURRAY BASIN; ISOTOPES; GROUNDWATER AGE; Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен